2018
DOI: 10.3389/fpls.2017.02244
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Terpene Biosynthesis in Berries of Microvine Transformed with VvDXS1 Alleles

Abstract: Terpenoids, especially monoterpenes, are major aroma-impact compounds in grape and wine. Previous studies highlighted a key regulatory role for grapevine 1-deoxy-D-xylulose 5-phosphate synthase 1 (VvDXS1), the first enzyme of the methylerythritol phosphate pathway for isoprenoid precursor biosynthesis. Here, the parallel analysis of VvDXS1 genotype and terpene concentration in a germplasm collection demonstrated that VvDXS1 sequence has a very high predictive value for the accumulation of monoterpenes and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 95 publications
(142 reference statements)
0
15
0
Order By: Relevance
“…Wild-type Muscat VvDXS1 (with increased catalytic efficiency) alleles were overexpressed in the “microvine,”, “Chardonnay,” and “Brachetto” cultivars. At flowering, the transgenic plants showed the upregulation of the HDR gene and of three genes of the MVA pathway compared to those of the control plants, suggesting that both pathways could be more deeply integrated than previously thought (Chaurasiya et al, 2012; Dalla Costa et al, 2018). In addition, genes from the downstream carotenoid, monoterpene, and sesquiterpene pathways were slightly upregulated compared to those of the control plants.…”
Section: Metabolic Engineering For Fruit Quality Traitsmentioning
confidence: 69%
See 3 more Smart Citations
“…Wild-type Muscat VvDXS1 (with increased catalytic efficiency) alleles were overexpressed in the “microvine,”, “Chardonnay,” and “Brachetto” cultivars. At flowering, the transgenic plants showed the upregulation of the HDR gene and of three genes of the MVA pathway compared to those of the control plants, suggesting that both pathways could be more deeply integrated than previously thought (Chaurasiya et al, 2012; Dalla Costa et al, 2018). In addition, genes from the downstream carotenoid, monoterpene, and sesquiterpene pathways were slightly upregulated compared to those of the control plants.…”
Section: Metabolic Engineering For Fruit Quality Traitsmentioning
confidence: 69%
“…Dalla Costa et al (2018) confirmed by analyzing a grapevine germplasm collection that the nucleotide changes in the sequence of VSDXS1 were able to explain the differential accumulation of monoterpenes in Muscat and non-Muscat grape varieties. In addition, this genetic variation seemed to also modulate sesquiterpene content.…”
Section: Metabolic Engineering For Fruit Quality Traitsmentioning
confidence: 80%
See 2 more Smart Citations
“…Like other compounds in this work, the concentration of terpene compounds under girdling was lower than that under cluster thinning. Previous reports have demonstrated that monoterpenes accumulation in grapevine berries were correlated with gene expression involved in MEP pathway, such as DXS, DXR, HDR, and GPPS 8,9,40,41 . However, in this study, only the expression level of VvDXS3 showed significant correlation with terpenes and linalool accumulation in all the four treatments from véraison to harvest.…”
Section: Discussionmentioning
confidence: 95%